Calculation and Analysis of Crack Stress Intensity Factor and J Integral of Helical Gear - Guangyao Sun; Mutellip Ahmat; Pengcheng Wang (Jixie chuandong)
The distribution of stress intensity factor and J integral of helical gear with three-dimensional crack under different initial crack parameters is studied. The finite element software is used to analyze the helical gear with initial crack. Three types of stress intensity factors and J integral at the elliptical crack tip of the dedendum are simulated and solved. The variation of the three stress intensity factors and J integral with the crack length， crack angle， crack position and other initial crack parameters is analyzed. The results show that when the data of different initial crack parameters are changed， the curves of the corresponding three stress intensity factors and J integral have obvious changing rules.